Dental Health of Youth in the World at the Current Stage (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article discusses the dental health of young people in the world today and the fight against oral diseases. It provides information based on examples and analyzes on how to keep teeth healthy in today's youth, the causes of disease, measures to prevent disease, and how young people should follow a healthy lifestyle to prevent oral cavity diseases.